Menilai Ulang Penafsiran Gunung yang Bergerak dalam QS. An-Naml [27]: 88: Analisis Epistemologis Berdasarkan Prinsip Verifikasi A. J. Ayer - Wardaniyanti (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
The interpretation of the "moving mountains" in Qur'an 27:88 has long generated debate within Qur'anic exegesis. Classical exegetes predominantly understand the verse as describing the cosmic events of the Day of Judgment, whereas a number of contemporary scholars interpret it as a scientific indication of the Earth's motion and geological dynamics. Although these interpretations have been extensively discussed from theological and scientific perspectives, limited attention has been devoted to examining their epistemological validity through the framework of modern philosophy of science. This study aims to reassess the interpretation of Qur'an 27:88 by applying Alfred Jules Ayer's verification principle as an epistemological framework for evaluating the scientific claims associated with the verse. Employing qualitative library research, the study analyzes primary Qur'anic commentaries, philosophical works on logical positivism, and contemporary scientific literature concerning Earth's rotation and geological processes. The analysis distinguishes between empirically verifiable propositions and metaphysical propositions in accordance with Ayer's concepts of meaningfulness, analytic and synthetic propositions, and strong and weak verification. The findings demonstrate that the proposition describing the apparent movement of mountains can be interpreted as an empirically meaningful statement when understood in relation to the Earth's rotational motion, whereas theological assertions concerning divine perfection remain beyond empirical verification and belong to the domain of metaphysical discourse. Rather than reducing the Qur'an to a scientific text, this study proposes an epistemological framework that clarifies the limits and possibilities of scientific interpretation within Qur'anic exegesis. By integrating Qur'anic studies, philosophy of science, and contemporary scientific knowledge, this research contributes a critical perspective for evaluating scientific interpretations of the Qur'an while preserving the distinction between empirical inquiry and metaphysical belief.